Exploring Contemporary Theodicies: Fresh Insights on the Problem of Evil in an Unjust World - Pane, Exson Eduaman (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2024)
The journal article titled "Exploring Contemporary Theodicies: Fresh Insights on the Problem of Evil in an Unjust World" investigates the problem of evil and injustice from a multidisciplinary perspective. The study reviews classical theodicies like the Augustinian, Irenaean, and Leibnizian approaches, which attempt to reconcile the existence of evil with an all-powerful, benevolent God. It also explores modern theodicies, including process theology, the free will defense, soul-making theodicy, and open theism, offering alternative explanations for the problem of evil. Additionally, the article incorporates psychological, sociological, and ethical perspectives to address the social and individual dimensions of evil and injustice. The findings emphasize the importance of deeper theological reflection, the inclusion of interdisciplinary insights, and the promotion of social justice. They also stress the cultivation of compassion, empathy, and the nurturing of faith and hope. The study calls for further research on topics such as comparative theodicies, the lived experience of evil, intersectionality, and theological perspectives on structural injustice. Ultimately, this research provides fresh insights into the problem of evil, fostering ongoing dialogue in theology, philosophy, and interdisciplinary studies, with an emphasis on justice, love, and mercy.